PERAN AUDIT SYARIAH DALAM PENGAWASAN PRAKTIK SHARIAH COMPLIANCE PADA LEMBAGA KEUANGAN SYARIAH - Misbah Misbah; Mustakim Muchlis; Roby Aditiya (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to find out how the Role of Sharia Audit in Supervision of Shariah Complince at Bank Syariah Indonesia (KCP) Bima City. By focusing on three main topics of discussion, namely the role of the shariah compliance audit, the shariah audit framework, and the concept of monotheism contained in the shariah compliance audit. The research method used in this research is qualitative with a phenomenological approach. The informants from the Indonesian Sharia Bank (KCP) Bima City consisted of two informants, namely the Leader and the Branch Operational and Service Manager. The data used in this study is primary data obtained through direct interviews with informants and secondary data is data obtained from internet data. The results of this study indicate that, the role of shariah compliance audit at the Bank Syariah Indonesia Office (KCP) Bima City is the supervision of financial statements. Furthermore, in the implementation of the sharia audit framework at the Indonesian Sharia Bank Sub-Branch Office of Bima City, the guidelines on the DSN MUI fatwa for audits outside of the financial aspect and sharia PSAK as guidelines in auditing financial statements. And the concept of monotheism contained in the shariah compliance audit at Bank Syariah Indonesia (KCP) Bima City is to apply an honest and trustworthy attitude in the implementation of the audit.